Physical Dating Violence, Sexual Violence, and Unwanted Pursuit Victimization: A Comparison of Incidence Rates Among Sexual-Minority and Heterosexual College Students. (February 2015) - Edwards, Katie M.; Sylaska, Kateryna M.; Barry, Johanna E.; Moynihan, Mary M.; Banyard, Victoria L.; Cohn, Ellen S.; Walsh, Wendy A.; Ward, Sally K.
The purpose of this study was to estimate the 6-month incidence rates of sexual assault, physical dating violence (DV), and unwanted pursuit (e.g., stalking) victimization among sexual-minority (i.e., individuals with any same-sex sexual experiences) college students with comparison data from non-sexual-minority (i.e., individuals with only heterosexual sexual experiences) college students. Participants ( N = 6, 030) were primarily Caucasian (92.7%) and non-sexual-minority (82.3%). Compared with non-sexual-minority students (N-SMS; n = 4, 961), sexual-minority students (SMS; n = 1, 069) reported significantly higher 6-month incidence rates of physical DV (SMS: 30.3%; N-SMS: 18.5%), sexual assault (SMS: 24.3%; N-SMS: 11.0%), and unwanted pursuit (SMS: 53.1%; N-SMS: 36.0%) victimization. We also explored the moderating role of gender and found that female SMS reported significantly higher rates of physical DV than female N-SMS, whereas male SMS and male N-SMS reported similar rates of physical DV. Gender did not moderate the relationship between sexual-minority status and victimization experiences for either unwanted pursuit or sexual victimization. These findings underscore the alarmingly high rates of interpersonal victimization among SMS and the critical need for research to better understand the explanatory factors that place SMS at increased risk for interpersonal victimization.